PENGARUH KADAR BA DAN 2.4-D TERHADAP VARIASI SOMAKLONAL KULTUR TUNAS BAWANG MERAH (Allium cepa L. Kelompok Agregatum) DAN BAWANG WAKEGI (Allium x wakegi Araki) - , KRISNA DHARMAYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Shallot (Allium cepa L. Aggregatum group, 2n = 16, AA) and wakegi onion (Allium x wakegi Araki, 2n = 16, AF) are vegetable crops in Indonesia which has long been intensively cultivated by farmers. Shallot and wakegi onion are generally propagated vegetatively by bulbs. Propagation by bulb in the same variety in a long term can reduce crop productivity and genetic diversity, moreover wakegi onion can not produce flower. Therefore, the reduction of genetic diversity will be high. The aims of the research were to increase diversity of shallot (Philip, Tiron, and Biru) and wakegi onion (Palasa and Palu) crops through somaclonal variation in a combination of BA and 2,4-D (ppm): (0-0, 2-2, 2-4, 4-2, and 4-4) by shoot culture. The research was conducted at the Tissue Culture Laboratory, Faculty of Agriculture, Gadjah Mada University in February 2012 to November 2012. Completely randomized block design with a factorial treatment combinations of cultivars and growth regulators was used. Somaclonal variation can be found from the observation of callus and increasing the number of chromosomes from diploid status (2n = 16). Observations support of the growth and development of explants during incubation includes number of shoots, number of leaves, leaf color, and the number of roots. The results showed that the treatment combination of BA and 2,4-D induced somaclonal variations through the changing of chromosomes number in callus stage. Somaclonal variations in shallot were trisomic, tetrasomic, and triploid cells from callus. The trisomic (2n = 16 +1) was in the treatment of Tiron 4ppm BA 2,4-D + 2ppm and 4ppm Biru BA +4 ppm 2,4-D. Tetrasomic (2n = 16 +2) was in the treatment of BA + 2ppm Philip 2ppm 2,4-D and BA 4ppm Tiron 4ppm + 2,4-D. The triploid (2n = 24) was in the treatment of Philip 2ppm BA +2 ppm 2,4-D. Somaclonal variations were not identified in wakegi onion callus. The explants without callus development were not identified somaclonal variation.